PROSPECTS OF DISTANCE LEARNING, IN RELATION TO THE NEW REALITIES OF SOCIO-ECONOMIC RELATIONS - P. A. Kapyrin (Вестник университета)
The article proposes the author’s view on global trends associated with new realities, caused by the COVID-19 pandemic, the consequences of which the world is aware of now and will finally accept after the end of the coronavirus pandemic. The paper focuses on the processes that probably await higher education in the near future and the requirements that will be imposed on it by the new socio-economic reality. The author emphasizes the main advantages and disadvantages of distance learning and the prospects for its development in the emerging new realities of social relations in society. The study evaluates the weaknesses of distance learning and proposes ways to overcome them to improve the effectiveness of distance learning.